PARTISIPASI KELOMPOK PEMUDA DALAM PENGEMBANGAN BISNIS PARIWISATA ISLAMI DI KOTA BANDA ACEH - Mirza Fanzikri, Mirza Fanzikri (IAIN Langsa, 2016)
Abstract.The objective of the research with the title, ?The Participation of Youth Groups in the Business Development of the Islamic Tourism in Banda Aceh,? is 1) to find out the condition of the business Islamic tourism in Banda Aceh, 2) to analyze the participation of youth groups in the businessdevelopment of the Islamic tourism in Banda Aceh, and 3) to formulate the strategy and policy of the participation of youth groups in the development of the Islamic tourism in Banda Aceh.Primary data were gathered by conducting in-depth interview with key informants, using purposive sampling technique. Qualitative approach was used to answer the first and the second problem formula in matching the theory with the fact in the field. Two different methods were used to answer the two formula strategy and policy: SWOT analysis was used to formulate strategy, and content analysis was used to answer the formula of policy in which Qanun design (Regional Regulation), RIPPDA (Master Design of the Development of Regional Tourism), Banda Aceh in the period of 2012-2017 was analyzed.The conclusion of the research was 1) the business development of the Islamic tourism in Banda Aceh over the last five years is increasing and developing, 2) participation of youth groups in the businessdevelopment of the Islamic tourism in Banda Aceh that were examined in the stage of planning, implementation, utilization, and evaluation is generally in the form of idea and energy, but participation in the form of providing goods and money is not found, and 3) government strategy in increasing the participation of youth groups in the development of the Islamic tourism in Banda Aceh is top-down by establishing groups of people and youth to promote and perform tourism counseling and formulating RIPPDA of Banda Aceh.Keywords: Participation of Youth Group, Development of the Islamic Tourism, Banda Aceh